Set it up and follow the steps:
6f - 15 = 3 (then add 15 to each side to isolate the f's from the known numbers)
6f = 18 (then divide both sides by 6 to solve for f)
f = 3
prove by substituting 3 for f:
6(3) - 15 = 3
18 - 15 = 3
3 = 3
You've given the answer yourself. d=6 and f=3.
If: df+10f = 3 Then: f(d+10) = 3 And: d = 3/f -10
The idea is to replace every "x" by "3", and then do the calculations.
20 equals Y that RVWS
The slope of f(x) = 3-4x is -4.
-2
You've given the answer yourself. d=6 and f=3.
f = 54
If: df+10f = 3 Then: f(d+10) = 3 And: d = 3/f -10
The idea is to replace every "x" by "3", and then do the calculations.
3 Coins in a Fountain
20 equals Y that RVWS
3-e = 4-f f-e = 4-3 f-e = 1
The slope of f(x) = 3-4x is -4.
I am assuming that k is the constant of proportionality so that f = k*a*t/b2 = 3*4*6/22 = 18
It is 1.2164
3